Imaging the neural correlates of tinnitus: a comparison between animal models and human studies - Middleton, Jason W.; Tzounopoulos, Thanos (Frontiers in Systems Neuroscience, 2012)
Tinnitus is the perception of a sound, a so-called “phantom sound”, in the absence of a physical sound. The phantom perception persists after transection of the auditory nerve, indicating that the site of tinnitus manifestation is in the central nervous system. Imaging studies in tinnitus sufferers have revealed increased neuronal activity -- hyperactivity -- in subcortical and cortical auditory centers. They have also demonstrated that non-auditory brain areas, such as the limbic system, are involved in the neural basis of tinnitus, Moreover, human imaging studies have led to novel hypotheses for the generation of tinnitus, such as the thalamocortical dysrhythmia hypothesis. Findings from imaging in animal models of tinnitus exhibit similarities to results from human studies and have also corroborated the involvement of hyperexcitability of auditory brain centers from physiological studies in animal models. We propose that the comparison between animal model and human studies will aid in the design of appropriate experimental paradigms aimed at elucidating the etiology of tinnitus. This will further our understanding of the neural basis of tinnitus and help better understand the possible role of aberrant cortical rhythms and the involvement of non-auditory brain centers in the development and establishment of tinnitus.